2019
DOI: 10.5545/sv-jme.2019.6297
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Machining Parameters on the Surface Porosity of a Closed-Cell Aluminium Foam

Abstract: Aluminium foam elements foamed into moulds, have a porous core, surrounded by a thin layer of non-porous outer surface. This layer affects the homogeneity and mechanical properties of the element significantly. To produce functional elements, the foams can be machined to a desired end shape. Machining deforms the surface structure, which results in a reduction of strength properties. This article describes an experimental approach to determine the effects of machining parameters on the surface porosity of clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Further application of the proposed edge extraction algorithm in other similar problems is encouraged, to evaluate further the algorithm's usability. The authors encourage the use of developed methods in macroscopical problems, such as determination of aluminium foam cells size [21] and similar ones in the Image Processing and Measurements domain [22]. The authors also encourage further assessment of BE and BE+ robustness, since these two simple procedures were only tested on 20 sample images overall.…”
Section: Discussionmentioning
confidence: 99%
“…Further application of the proposed edge extraction algorithm in other similar problems is encouraged, to evaluate further the algorithm's usability. The authors encourage the use of developed methods in macroscopical problems, such as determination of aluminium foam cells size [21] and similar ones in the Image Processing and Measurements domain [22]. The authors also encourage further assessment of BE and BE+ robustness, since these two simple procedures were only tested on 20 sample images overall.…”
Section: Discussionmentioning
confidence: 99%
“…Metallurgical and morphological (Zhu et al 2018;Yilbas et al 2014Yilbas et al , 2013Yilbas et al , 2015 observations have revealed that cutting process affects porous material's mechanical properties significantly. Various processing and machining parameters such as deformation depth, feed rate, spindle speed (Razboršek et al 2019) in incremental forming and frictional rolling method as well as laser power, scanning speed, gas pressure, cutting forces, and cutting temperatures (Liu et al 2020) in laser cutting techniques have been previously investigated thoroughly. For instance, Heidari and Yan used single-crystal diamond tools for cutting, and realized that the presence of pores affects the accuracy of cutting mechanism directly (Heidari and Yan 2018).…”
Section: Methodsmentioning
confidence: 99%